Nonlinear intersubband THz absortion in asymmetric quantum well structures (2004)
"Semiconductor devices are a very important sou.rce Of electromagnetic (ENI) waves daily life applications. In one extreme; the, visible and infrared (IR) Insers are at the core of informntion technology. In the Other, microwave and radio frequency elliitt,ers make possible wireless communications. But in the THz region of the EM spectrum, thai spans from 100GHz to 10THz, there is an scarcity of compact solid-state sources thai operate at room temperature. But in present times there is a need for such devices as a relatively long list of applications has been envisioned for the THz range: chernical detection, astronomy, wireless communications, atmospheric sensing, dental, biological and medical imaging are among the possible applications for this region. Another set of interesting experiments in the T Hz range are t,he Tllz Time Domain Spectroscopy (TH' TDS) experirnents. These works are illipoñant in both fundarnental research and realworld applications..."-- Tomado de la Introducción.